2010
DOI: 10.1186/1471-2407-10-369
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of stromelysin-1 (matrix metalloproteinase-3) promoter (-1171 5A->6A) polymorphism in oral submucous fibrosis and head and neck lesions

Abstract: BackgroundMatrix metalloproteinases (MMPs) are enzymes that degrade all the components of extra cellular matrix and collagen. Various types of MMPs are known to be expressed and activated in patients with oral submucous fibrosis (OSMF) as well as head and neck squamous cell carcinoma (HNSCC). The purpose of this study was to asses the association of the single nucleotide polymorphism (SNP) adenosine insertion/deletion polymorphism (-1171 5A->6A) in the MMP-3 promoter region in these lesions.MethodsMMP-3 SNP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…They may include damage to the ECM proteins, alterations in the mechanisms responsible for inhibition of the calcification process, and abnormalities in the mitochondrial calcium and phosphate levels (Gutierrez and Wetter, 2012). It has been previously reported that the 6A allele has two-folds lower promoter activity than the 5A allele (Chaudhary et al, 2010). This lower transcriptional activity may be responsible for protecting against calcinosis development in SSc patients with the 6A/6A genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may include damage to the ECM proteins, alterations in the mechanisms responsible for inhibition of the calcification process, and abnormalities in the mitochondrial calcium and phosphate levels (Gutierrez and Wetter, 2012). It has been previously reported that the 6A allele has two-folds lower promoter activity than the 5A allele (Chaudhary et al, 2010). This lower transcriptional activity may be responsible for protecting against calcinosis development in SSc patients with the 6A/6A genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the -1171 position of the MMP3 promoter region, an insertion of one adenosine gives rise to alleles having either six (6A) or five adenosines (5A); it has been previously reported that individuals with the 6A/6A genotype may have decreased MMP-3 expression (Chaudhary et al, 2010). Finally, MMP9 harbors a C-to-T transition at the -1562 position; the T allele has been associated with higher transcriptional activity compared to the C allele (Skarmoutsou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to the study conducted by Choudhary et.al, which showed a significant difference in 5A allele frequency between OSF and HNSCC as compared with controls. The study concluded that the 5A genotype had a more than two fold risk for OSF (OR = 2.26) and little less in HNSCC (OR = 1.94) in relation to the control group [28]. Association of Duration of the habit with stages of OSF were statistically significant p = 0.01 and p = 0.04 with 5A/5A, 5A/6A,6A/6A genotypes Thus the association of duration of the habit and stage of OSF was significant with the genotypes Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously conducted study by Choudhary et.al with the MMP-3 gene polymorphism in OSF and HNSCC there was a significant difference in the MMP-3 genotype distribution between the areca nut with tobacco chewers and the non -chewers both in OSMF and HNSCC [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation